Neuraxial Anesthesia for Cesarean Section in Pregnant Women with Ruptured Arteriovenous Malformation - Ida Bagus Reza Nanda Iswara; FX Adinda Putra Pradhana (HM Publisher, 2023)
Background: Maternal stroke as a result of ruptured arteriovenous malformation (AVM) in pregnancy is rare. However, AVM rupture can result in high morbidity during pregnancy and the puerperium. In its management, several special considerations are needed to ensure the welfare of the mother and fetus. This article will discuss anesthesia in pregnant patients after hemorrhagic stroke due to AVM rupture under neuraxial anesthesia. Case presentation: A 25-year-old patient with a second pregnancy with twins at 33 weeks came with complaints of water coming out of the birth canal 1.5 hours before admission to the hospital. The patient was diagnosed with G2P0010 33 Weeks 3 days Gemelli H/H head presentation, buttocks presentation, intracerebral hemorrhage (ICH) et cause suspected AVM rupture, premature rupture of membranes, and first-day febrile observation and planned to undergo cito cesarean section. Conclusion: Neuraxial anesthesia is one of the safe options for pregnant patients after a hemorrhagic stroke with controlled intracranial pressure.